Adoption and impact of dryseason dualpurpose cowpea in the semiarid zone of Nigeria - Inaizumi, H.; Singh, B.; Sanginga, P.; Manyong, Victor M.; Adesina, A.A.; Tarawali, Shirley A. (1999)
In the semiarid region of West and Central Africa, farmers traditionally cultivate different cowpea varieties for grain and fodder. However, the grain yield potential and the availability of good quality fodder is limited by several factors: insects, pests and diseases, low and erratic rainfall, and the long dry season. In the early 1990s, the International Institute of Tropical Agriculture (IITA), in collaboration with the International Livestock Research Institute (ILRI), initiated a breeding program to develop improved cowpea varieties that produce both grain for human consumption and fodder for livestock in the dry season. This paper examines the patterns, levels, rate of adoption, and the impact of one of the most promising varieties (IT89KD-288) introduced to farmers in Kano State, Nigeria. The diffusion and uptake of this variety had been very impressive as it reached over 1500 farmers in 1997, only 4 years after its accidental release to one farmer. The results show that farmers derived substantial benefits from adopting dry-season dual-purpose cowpea. These include food security during a critical period of the year, cash income, crop diversification, fodder, and in situ grazing after harvesting, in periods when the prices of cowpea grain peak, and when good quality fodder is scarce. Dry-season dual-purpose cowpea is thus a profitable technology that will find economic and ecological niches in the mixed crop/livestock farming systems of the semiarid zones of West and Central Africa.